A mechanically robust, fully zwitterionic photothermal hydrogel with superhydrated interfaces for antifouling desalination - Keyang Shen; Yunpeng Zhu; Haiyang Wang; Jingtao Bi; Lei Wang; Zhiyuan Guo; Jing Wang; Panpan Zhang; Zhi-Yong Ji (Chemical Engineering Journal, 2026)

Numerical investigation of thermodynamic effect on cavitation performance and cavitation-vortex interaction in an inducer - Bin Xu; Xingyu Liu; Keyang Liu; Weibin Zhang; Yilin Deng; Xi Shen; Desheng Zhang; B.P.M (Bart) van Esch (Ocean Engineering, 2024)

Thermodynamic effect on attached cavitation and cavitation-turbulence interaction around a hydrofoil - Bin Xu; Keyang Liu; Jiali Deng; Xingyu Liu; Xi Shen; Desheng Zhang; Ailian Chang; Jiuyu Chen; Sijiang Chang (Ocean Engineering, 2023)

Experimental Study on Unsteady Cavitating Flow and Its Instability in Liquid Rocket Engine Inducer - Hao Wang; Jian Feng; Keyang Liu; Xi Shen; Bin Xu; Desheng Zhang; Weibin Zhang (Journal of Marine Science and Engineering, 2022)
To study instability in the unsteady cavitating flow in a liquid rocket engine inducer, visualization experiments of non-cavitating and cavitating flows inside a model inducer were carried out at different flow conditions. Visual experiments were carried out to capture the evolution of non-cavitating and cavitating flows in a three-bladed inducer by using a high-speed camera. The external characteristic performance, cavitation performance, and pressure pulsation were analyzed based on the observation of non-cavitation and cavitation development and their instabilities. Under non-cavitation conditions, the change of flow rate has a significant impact on the pressure pulsation characteristics in the inducer. The occurrence of cavitation aggravated the instability of the flow and caused the intensity of pressure pulsation at each measuring point to increase. This cavitation structure has strong instability, and the tail region is often accompanied by shedding cavitation clouds perpendicular to the blade surface.

A Mechanistic Pharmacokinetic Model Elucidating the Disposition of Trastuzumab Emtansine (T-DM1), an Antibody–Drug Conjugate (ADC) for Treatment of Metastatic Breast Cancer - Brendan Bender; Douglas D. Leipold; Keyang Xu; Ben-Quan Shen; Jay Tibbitts; Lena E. Friberg (The AAPS Journal, 2014)